Alternative vascular constructs of lymph node flap transfer - (:unkn) unknown (WILEY, 2018)
Vascularized lymph node transfer is a quite innovative physiological surgical procedure for the lymphedema treatment. Although is gaining more popularity due to its promising results, there are some concerns regarding difficult to harvest it and the potential risk of iatrogenic lymphedema. Here, we present alternative vascular constructs of lymph node flap for the treatment of lymphedema, which provide the benefits of a technically easier dissection and physiological reconstruction of the damaged lymphatics. Furthermore, we introduce a classification based on the flap vascular supply including six types of flaps and we provide the details of the surgical technique.
Keywords: lymph node flap; lymphedema; microsurgery; LIMB LYMPHEDEMA; TRANSPLANTATION